2.5-dimensional VLSI system integration. - Yangdong Deng (IEEE Transactions on VLSI systems)
The excessive interconnection delay and fast increasing development cost, as well as complexity of the single-chip integration of different technologies, are likely to become the major stumbling blocks for the success of monolithic system-on-chips. To address the above problems, this paper investigates a new VLSI integration paradigm, the so-called 2.5-dimensional (2.5-D) integration scheme. Using this scheme, a VLSI system is implemented as a three-dimensional stacking of monolithic chips. A cost analysis framework was developed to justify the 2.5-D integration scheme from an economic point of view. Enabling technologies for the new integration scheme are also reviewed.